Leadership of The Head of Madrasah in Carrying Out Academic Supervision To Improve Teacher Performance at MA Hidayatul Mubtadiin - Sri Lestari; Cipto Handoko; An An Andari; Iskandar Zulkarnain (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The head of the madrasa plays a strategic role in improving the quality of education in madrasahs, especially the quality of educators or teachers. Teacher As a person who is at the forefront and responsible for the development and progress of students. This study aims to find out how the leadership of the head of the madrasah through academic supervision to improve teacher performance at MA Hidayatul Mubtadiin Jatiagung. In this study, qualitative research methods were used. Data collection methods are in the form of observation, interviews and documentation. Data analysis includes data collection, data provision, and drawing conclusions. The results showed that the implementation of basic supervision in improving teacher performance at Ma Hidayatul Mubtadiin Jatiagung, In planning the supervision program, the principal had done a good job of planning, but there were still shortcomings. This is known from data showing that the supervision program is planned twice a year. Program planning has been well communicated with the teacher council. In implementing the supervision program, the principal has carried out class visits in accordance with the schedule and supervision assessment sheets that have been approved by the teacher council and the principal. However, in providing guidance on the manufacture of learning tools, it is not optimal. In the follow-up supervision, the principal did not analyze the findings of the supervision. The principal also did not make any findings back as reinforcement after supervision. Thus, follow-up supervision is not optimal.